Sistem Informasi Inventarisasi Barang pada PMI Kota Jambi - Novika, Novika; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2024)
The inventory information system used by the Indonesian Red Cross in Jambi City still uses a manual system, namely by using Microsoft Office Excel so that the search for inventory data is slow. Therefore, this final project is carried out to make the analysis and design of a web-based goods inventory system that is easy to use, so that it can facilitate access to the desired information and can make it easier to manage data or files. The research of this final project is to design and analyze a web-based Goods Inventory Information System at the Indonesian Red Cross in Jambi City. For this reason, this research will analyze and design the information system using the Balsamiq Mockups 3.5.15 application. So that in the end the results of the analysis and design of this information system will be used by programmers to implement it.